ВИЗНАЧЕННЯ ОПТИМАЛЬНИХ ПАРАМЕТРІВ НАКОПИЧУВАЧІВ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ ТА ГЕНЕРУЮЧИХ ДЖЕРЕЛ В АВТОНОМНИХ ЛОКАЛЬНИХ ЕЛЕКТРОСИСТЕМАХ - Сивенко, М.М.; Мірошник, О.О. (Інститут електродинаміки Національної академії наук України, 2023)
The problem of determining the optimal parameters of electric energy storage and generating sources in autonomous local power systems is presented. A detailed justification of the role of electricity storage in the presence of renewable energy sources in autonomous local power systems with a stochastic mode of operation is given. The main provisions of the used model of autonomous local electrical systems are given. The dependence of the electricity storage parameters depending on the composition of the generation was investigated. The implementation of the task of determining the parameters of electricity storage devices by the method of targeted simulation is considered. The results of the multi-criteria selection of the power and energy capacity of the electricity storage unit using economic criteria are determined. A mathematical model for determining the optimal parameters of electric energy storage for autonomous local electrical systems using mixed integer programming with optimization based on economic indicators has been developed. The dependence of the parameters of electric energy storage devices on the composition of the generation of autonomous local electrical systems has been studied.